(NON-)INCLUSIVE LANGUAGE IN THE SPANISH CRIMINAL CODE. ANALYSIS AND PROPOSAL - Rodríguez-Vázquez, Rosalía (2024)
Inclusive language is the type of language that uses a range of grammatically sound formulae to encourage a vision of the world in which both women and men are included in order to overcome linguistic sexism and androcentrism. The consistent use of inclusive language de-masculinises job-market realities that have traditionally been dominated by males, as is the case of the legal professions. In Spain, the legal field has changed drastically in the last decades, to the extent that more than half of the judges and magistrates in the country are female. Despite that, the legal codes on which sentences are based have not evolved with regard to the use of inclusive language. This paper presents the results of the systematic analysis of gender-marked lexicon in the Spanish Criminal Code (1995, last modified 2023). The quantitative and qualitative analysis of the Code allows us to draw some conclusions regarding a) the overwhelming presence of non-inclusive or gender-biased terms, and b) the frequency of use of each of those terms and its implications. The data obtained indicate that the Spanish Criminal Code is biased for gender inasmuch as it resorts to masculine forms in almost 100% of the cases. As a feasible alternative, this article introduces some language suggestions to make the Criminal Code more neutral and inclusive.